Data Envelopment Analysis A Handbook of Models and Methods - Zhu, Joe (Springer, 2015)
This handbook complements the second edition of the Handbook on Data Envelop ment Analysis (Cooper et al. 2011, Springer). Data envelopment analysis (DEA) is a “data-oriented” approach for evaluating the performance of a set of entities called Decision Making Units (DMUs) whose performance is categorized by multiple met rics. These performance metrics are indicated as inputs and outputs under DEA. Although DEA has a strong link to production theory in economics, the tool is also used for benchmarking in operations management where a set of measures is se lected to benchmark the performance of manufacturing and service operations. In the circumstance of benchmarking, the efficient DMUs, as defined by DEA, may not necessarily form a “production frontier,” but rather lead to a “best-practice frontier” (Cook et al. 2014)...